Maximally accreting supermassive stars: a fundamental limit imposed by hydrostatic equilibrium - Haemmerlé, Lionel; Klessen, Ralf S. (Astronomy and astrophysics, 2019)
Context: Major mergers of gas-rich galaxies provide promising conditions for the formation of supermassive black holes (SMBHs; ≳105 M⊙) by direct collapse because they can trigger mass inflows as high as 104 − 105 M⊙ yr−1 on sub-parsec scales. However, the channel of SMBH formation in this case, either dark collapse (direct collapse without prior stellar phase) or supermassive star (SMS; ≳104 M⊙), remains unknown. Aims: Here, we investigate the limit in accretion rate up to which stars can maintain hydrostatic equilibrium. Methods: We compute hydrostatic models of SMSs accreting at 1–1000 M⊙ yr−1, and estimate the departures from equilibrium a posteriori by taking into account the finite speed of sound. Results: We find that stars accreting above the atomic cooling limit (≳10 M⊙ yr−1) can only maintain hydrostatic equilibrium once they are supermassive. In this case, they evolve adiabatically with a hylotropic structure, that is, entropy is locally conserved and scales with the square root of the mass coordinate. Conclusions: Our results imply that stars can only become supermassive by accretion at the rates of atomically cooled haloes (∼0.1 − 10 M⊙ yr−1). Once they are supermassive, larger rates are possible.